Old Paradigms in a New Curriculum: How Indonesian Language Teachers Perceive Learning Assessment under the Merdeka Framework - Siti Hamidah; Vismaia S. Damaianti; Andoyo Sastromiharjo; Yeti Mulyati (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
Curriculum reform is only as transformative as the paradigms teachers bring to its implementation. The Merdeka Curriculum places assessment at the core of the learning process, demanding a decisive departure from older, obligation-driven, summative paradigms toward integrated, formative, and student-centred orientations. Yet whether Indonesian language teachers have genuinely abandoned their prior assessment paradigms or continue to operate within them despite a new curricular mandate remains empirically underdocumented. This study examines how Indonesian language teachers at the junior secondary level perceive learning assessment under the Merdeka Curriculum, focusing on their understanding of assessment principles, curriculum orientation, and the three foundational assessment orientations: Assessment of Learning (AoL), Assessment for Learning (AfL), and Assessment as Learning (AaL). Using a qualitative descriptive design, structured interviews were conducted with teachers from five public junior secondary schools (SMP Negeri) in Bandung City. Data were analysed through the Miles and Huberman interactive model  encompassing data reduction, data display, and conclusion drawing  with trustworthiness ensured through member-checking and researcher triangulation. The findings reveal a consistent pattern: despite operating under a new curriculum, the majority of teachers continue to govern their assessment practice through an old paradigm that treats assessment as a bureaucratic obligation tied to formal examination schedules rather than as a holistic, ongoing component of the learning continuum. Most teachers demonstrated limited understanding of the Merdeka Curriculum’s five assessment principles and of the AoL/AfL/AaL orientations, and showed minimal engagement with self-assessment and peer assessment. These findings confirm that old paradigms are both real and pervasive, and underscore the urgency of targeted professional development to bring teachers’ assessment practice into genuine alignment with the Merdeka Framework.